The first steps of the Clinical Neurology in South America - Allegri, Ricardo Francisco (2013)
The field of neurology in South America began to emerge toward the end of the 19th century, following the origin of the specialty in Europe. There was a consistent and long-standing admiration for European training, which led to the birth of the discipline in South America. The first steps took place almost simultaneously with European countries in Argentina, Brazil, Uruguay, Chile, and Peru. In the other countries, the development of neurology took place later in the 20th century.